Divergent trends in the incidence and mortality of acute myocardial ischaemic syndrome, especially in women. Evidence from Finland in 1996–2021 - Atte Kallström; Ida Holopainen; Oleg Kambur; Markus Perola; Veikko Salomaa; Aki S. Havulinna; Markus Ramste; Juha Sinisalo (Annals of Medicine)
Objective Although the incidence and case fatality (CF) of acute myocardial ischaemic syndrome (AMIS) have declined in recent decades, some studies have suggested a potential stagnation in this decline. We examined if a similar development in AMIS trends can be observed in Finland from 1996 to 2021 among persons aged 35–74 years.Methods We linked Finnish country-wide Hospital Discharge- and Causes of Death- Registers covering the first non-fatal and fatal myocardial ischaemic events (total 69 906 442 person-years at risk). We analyzed the incidence, mortality, and 28-day CF and their trends using negative binomial, Poisson, segmented and logistic regression adjusting for age and sex.Results The analysis consisted of 186 489 non-fatal and 72 907 fatal myocardial ischaemic events. AMIS incidence declined in men (annual percentage change (APC) −2.0%) and in older women (APC of 55–64 years −1.5%; 65–74 years −3.3%) during the study period. However, the incidence decline slowed down over the last decade in oldest age groups and stopped overall in women. Incidence was unchanged during the study period in younger women aged 35-54 years. AMIS mortality and CF declined (APC of mortality in men −4.4%; in women −5.0%; APC of CF in men −2.7%; in women −3.3%).Conclusions AMIS mortality declined in all groups, but the decline in AMIS incidence slowed down and even stopped in women. Incidence was unchanged during the study period in women aged 35-54 years. These results emphasize the need for further efforts in prevention of cardiovascular disease, particularly in young and middle-aged women.